1982
DOI: 10.1161/01.res.50.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pericardium on left ventricular end-diastolic pressure-segment relations during early and later stages of experimental chronic volume overload in dogs.

Abstract: SUMMARY. Although the pericardium can exert a restraining effect on filling of the normal left ventricle, it is uncertain to what extent the pericardium influences left ventricular filling during chronic volume overload. We measured left and right ventricular pressure and left ventricular segment dimension before and after pericardiectomy over a range of left ventricular end-diastolic pressure from <5 to >20 mm Hg in open-chest dogs with volume overload due to a prior systemic arteriovenous fistula. In six dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 26 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Whereas it was not the intent of the current studies to determine the role of the percardium in ventricular interaction, the extent to which the pericardium absolutely affects this interaction in the normal heart may limit the general application of our results. The role of the pericardium in abnormal, chronically dilated hearts is even less well understood, although studies in a chronically volume overloaded canine model suggested that the pericardium dilated to accommodate the chronic cardiac dilation and markedly diminished the restrictive effects of the pericardium on ventricular filling (LeWinter and Pavelec, 1982). A more precise quantification of the role of the pericardium in ventricular interaction in the normal conscious dog model awaits development of techniques that do not abnormally alter its physiology-…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it was not the intent of the current studies to determine the role of the percardium in ventricular interaction, the extent to which the pericardium absolutely affects this interaction in the normal heart may limit the general application of our results. The role of the pericardium in abnormal, chronically dilated hearts is even less well understood, although studies in a chronically volume overloaded canine model suggested that the pericardium dilated to accommodate the chronic cardiac dilation and markedly diminished the restrictive effects of the pericardium on ventricular filling (LeWinter and Pavelec, 1982). A more precise quantification of the role of the pericardium in ventricular interaction in the normal conscious dog model awaits development of techniques that do not abnormally alter its physiology-…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of ventricular dimensions, indicating augmentation of total intrapericardial volume, combined with the decline in transpericardial pressure, implied an increase in pericardial compliance. These data provide information regarding the time course of pericardial relaxation over the period intermediately between acute, open-chest studies (Glantz et al, 1978;Stokland et al, 1980) and the more recent work regarding pericardial creep in long-term studies of chronic volume overload (LeWinter et al, 1982). Thus, in addition to the length, placement, and precise closure of the pericardiotomy, pericardial retraction may account for the divergent results among various studies.…”
Section: Discussionmentioning
confidence: 85%
“…Data from the dogs studied sequentially suggested that substantial limitation of ventricular filling was present immediately after instrumentation but reversed with time. This early restraining effect may have been related to pericardial retraction occurring during instrumentation, and reversal of this effect may be analogous to pericardial creep (Rabkin et al, 1974;LeWinter et al, 1982). As illustrated by data from one of these dogs (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The pericardium, however, can grow and therefore adapt to chronic increases in cardiac volume; 16 it therefore was assumed that although pericardial constraint and DVI might be important in acute situations, they were unlikely to be important in chronic HF. This was shown to not be the case.…”
Section: Why Is This Important?mentioning
confidence: 99%